(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Breast cancer is one of the leading causes of death among women, making early detection through breast self-examination (BSE or SADARI) a simple yet crucial preventive strategy. Surveys conducted in several secondary schools revealed that most adolescent girls lack awareness of the importance of SADARI and have never practiced it. This low level of knowledge is influenced by factors such as embarrassment, the perception that breast cancer only affects adults, and limited health education in schools. Therefore, educational interventions through school-based health promotion are necessary to enhance adolescents’ understanding of BSE.This Community Service Program aimed to improve adolescent girls’ knowledge of SADARI through structured health promotion activities at SMP Trisakti Lubuk Pakam. The program employed a one-group pretest-posttest design, involving 20 female students selected using purposive sampling. Instruments included a BSE knowledge questionnaire, educational media such as presentations, leaflets, and visual aids, as well as activity monitoring sheets. Implementation stages comprised preparation, pretest, educational intervention, posttest, and follow-up activities.The results showed a significant increase in mean knowledge scores from 5.2 (low category) before the intervention to 8.1 (high category) after the intervention, with a gain of 2.9 points. The distribution of knowledge categories also shifted positively: the proportion of participants in the good category increased from 25% to 70%, the very good category from 5% to 25%, while the moderate category decreased from 65% to 5%, and no participants remained in the poor category. In conclusion, this health promotion program effectively enhanced adolescent girls’ knowledge of SADARI, supporting early breast cancer detection independently and sustainably.